“Pattern Failure and Five-Year Overall Survival in Locally Advanced Cervical Cancer: A Systematic Review Comparing Concurrent Chemoradiotherapy vs Radiotherapy Only” - Nopianti, Tiara; Maulana, Muh. Iqbal; Suwartono, Herdhana; Nabelo, Rara (Ethiopian Journal of Reproductive Health, 2025)
Purpose: This systematic review aims to compare chemoradiotherapy (CRT) and radiotherapy (RT) failure patterns, particularly the incidence of distant metastases and overall survival outcomes, only in patients with locally advanced cervical cancer. Methods: Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a comprehensive literature search was conducted for articles published between January 1, 2020, and January 1, 2025. The search included the terms: "cervical cancer," "chemoradiotherapy," "radiotherapy," and "chemotherapy." Studies were selected based on their evaluation of CRT versus RT in patients with locally advanced cervical cancer, with specific attention to distant metastasis rates and overall survival. Results: Across multiple studies, CRT was associated with a lower incidence of distant metastases compared to RT. Olthof et al. reported 54% metastasis in the CRT group versus 80% in the RT group. Van den Akker et al. observed 37.2% in CRT versus 62.7% in RT. Kushwaha et al. found the lowest rates, with 10.5% in CRT compared to 19.8% in RT. However, results regarding overall survival were inconsistent. Van den Akker et al. reported higher 5-year survival in the RT group (66.8%) compared to CRT (50.1%). Olthof et al. found no significant difference, while Kushwaha et al. observed longer median survival in CRT (66 vs. 44 months), though not statistically significant (p = 0.087). Conclusion: Adjuvant CRT appears to reduce the risk of distant metastases in patients with high-risk LACC compared to RT alone. However, its impact on overall survival remains uncertain due to inconsistent and non-significant findings across studies.